Ensuring safe and effective pharmacotherapy: The role of “community pharmacology” in attaining “health for all” from the Indian perspective - Tirthankar Deb; Alapan Das; Bisweswar Ojha; Prasanjit Das (Journal of Family Medicine and Primary Care)
The novel approach of “Community Pharmacology” integrates pharmacological principles with community health to achieve the “Health for all” goal through safe and efficient health care. Pharmacovigilance, medication errors (ME), irrational prescriptions, and antimicrobial resistance in the community could be the key areas. Though life expectancy and other health indicators have improved in India, the disparity between rural and urban quality healthcare access should be addressed. Despite India’s enormous progress in vaccine manufacture, supply, and mass immunization through the Universal Immunization Programme (UIP) and Mission Indradhanush, issues remain in incomplete coverage and vaccine hesitancy. Other key challenges include high health expenditures, shortage of trained healthcare professionals, and lack of patient safety and irrational pharmacotherapy in remote areas. Community Pharmacology offers a multifaceted solution in community healthcare delivery through a well-designed integrated network equipped with skills in practical implications of pharmacology aimed at better medication supply, storage and dispensing, adherence to formularies according to the community needs, preparing Essential Medicine List and implementation of rational prescribing. Antimicrobial stewardship (AMS), adverse drug reaction (ADR) monitoring, and evidence-based usage of different drug formulations or drug delivery systems must be implemented beyond the tertiary level, involving both public and private stakeholders. Integrating Community Pharmacology into public health is crucial for fulfilling the global health initiatives to reach the Sustainable Development Goals (SDGs) as well as attaining India’s ambitious overall development targets.